2015
DOI: 10.2147/ndt.s91861
|View full text |Cite
|
Sign up to set email alerts
|

A review of cognitive conflicts research: a meta-analytic study of prevalence and relation to symptoms

Abstract: Recent research has highlighted the role of implicative dilemmas in a variety of clinical conditions. These dilemmas are a type of cognitive conflict, in which different aspects of the self are countered in such a way that a desired change in a personal dimension (eg, symptom improvement) may be hindered by the need of personal coherence in another dimension. The aim of this study was to summarize, using a meta-analytical approach, the evidence relating to the presence and the level of this conflict, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
3
18
0
2
Order By: Relevance
“…Los términos de búsqueda, el periodo de análisis y las fuentes consultadas siguen la metodología empleada en estudios previos (Montesano, López-González, Saúl y Feixas, 2015;Saúl et al, 2012). Para seleccionar los documentos originales primarios se empleó la siguiente ecuación de búsqueda en los campos título (TI), resumen (AB) o palabras clave (KW): [("date violence" OR "date abuse" OR "date aggression" OR "dating violence" OR "dating abuse" OR "dating aggression" OR "courtship violence" OR "courtship abuse" OR "premarital abuse" OR "premarital violence" OR "premarital aggression") AND ("prevalence" OR "incidence" OR "frequency")].…”
Section: Procedimiento De Búsquedaunclassified
“…Los términos de búsqueda, el periodo de análisis y las fuentes consultadas siguen la metodología empleada en estudios previos (Montesano, López-González, Saúl y Feixas, 2015;Saúl et al, 2012). Para seleccionar los documentos originales primarios se empleó la siguiente ecuación de búsqueda en los campos título (TI), resumen (AB) o palabras clave (KW): [("date violence" OR "date abuse" OR "date aggression" OR "dating violence" OR "dating abuse" OR "dating aggression" OR "courtship violence" OR "courtship abuse" OR "premarital abuse" OR "premarital violence" OR "premarital aggression") AND ("prevalence" OR "incidence" OR "frequency")].…”
Section: Procedimiento De Búsquedaunclassified
“…Research conducted so far on IDs has shown that they are significantly more prevalent in clinical samples than in controls ( OR = 3.43; Montesano et al, 2015) and especially in depression. Specifically, researchers reported percentages of 68.3% of patients with a diagnosis of major depression (Feixas et al, 2014a) and 69.6% in a sample with dysthymia (Montesano et al, 2014) in contrast to roughly a third of non-clinical individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Using the definition of cognitive conflicts as implicative dilemmas, several studies have found this notion clinically relevant to the understanding of psychological distress in a variety of different disorders. [9] Specifically, some authors indicate that the presence of implicative dilemmas was greater in people with depression than in control groups. [10,11] Moreover, depressed patients with implicative dilemmas presented lower levels of global functioning and more frequent history of suicide attempts.…”
Section: Introductionmentioning
confidence: 99%